2005
DOI: 10.1016/j.geoderma.2004.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Drainage, salt leaching and physico-chemical properties of irrigated man-made terrace soils in a mountain oasis of northern Oman

Abstract: Little is known about the sustainability of irrigated oasis agriculture in northern Oman. The objective of this study therefore was to examine which factors allowed agricultural productivity to be apparently maintained during the two millenia of a mountain oasis' existence. Soil moisture and physico-chemical properties were measured in a typical flood-irrigated field sown to alfalfa (Medicago sativa L.). Particle size, organic (C org ) and inorganic carbon content, pH and electrical conductivity (EC) of the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 20 publications
0
39
1
3
Order By: Relevance
“…Five Omani landraces were collected in the mountain oases of Balad Seet and Maqta in northern Oman, (Figure 1) where a hyperarid climate characterizes agriculture on tiny man-made terraces (Luedeling et al 2005). Approximately 500 g of recently harvested seed were sampled from the stock of a farmer known to grow a specific landrace (identified by its vernacular name).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Five Omani landraces were collected in the mountain oases of Balad Seet and Maqta in northern Oman, (Figure 1) where a hyperarid climate characterizes agriculture on tiny man-made terraces (Luedeling et al 2005). Approximately 500 g of recently harvested seed were sampled from the stock of a farmer known to grow a specific landrace (identified by its vernacular name).…”
Section: Plant Materialsmentioning
confidence: 99%
“…The precision of the ECH20 EC-20 is such that it can be used for greenhouse operations and to schedule field irrigation (Nemali et al 2007). The main benefit of the ECH2O sensor is that it is one of the most inexpensive probes available and therefore can be widely used and implemented (Christensen, 2005;Luedeling et al 2005;Riley et al 2006). The ECH2O sensor is designed to be buried in the soil for extended periods of time and connected to a data logger such as the Em5b (Decagon Devices, Pullman WA).…”
Section: Soil Moisture Measurementmentioning
confidence: 99%
“…The existing studies reported high application rates of organic fertilizer to the man-made terrace soils leading to the apparent accumulation of organic C despite very high emanation of gaseous C and N Buerkert et al 2010). Soil organic mater (SOM) not only supplies energy and nutrients for macro-microorganisms and plants, it also contributes to soil textural stability and water holding capacity (Nyberg et al 2006) thereby also governing drainage, a key component in irrigated agricultural systems (Luedeling et al 2005). The turnover of SOM is heavily controlled by the characteristics of organic matter (C/N ratio and the concentration of lignin and secondary metabolites such as tannins), soil properties (pH, clay content, redox potential), macro and microorganism communities, crop management practices, and by environmental factors (Kladivko et al 1987;Deng and Tabatabai 2000;De Neve and Hofman 2002;Agehara and Warncke 2005;Burgos et al 2006).…”
mentioning
confidence: 99%